Protecting customer funds for emerging financial products - Sunjoo Hwang (Korea Development Institute (KDI), 2024)
Emerging financial products driven by innovation, such as virtual assets and simplified payment services, introduce both new conveniences and in-transaction risks to customer funds. Despite regulations on segregating customer funds already in place, full compliance by businesses with these rules is unlikely, especially with insolvency on their horizon. This paper proposes a new protection framework that bolsters the safety of new financial products and reduces funding pressures for the compensation scheme.
Keywords: 330